Multiple bone fractures with a hidden aetiology-A case report (Journal of Pathology of Nepal, 2022)
A patient presented with fracture of multiple bones, on investigations, showed primary hyperparathyroidism due to an adenoma in the inferior parathyroid gland. The bones showed typical changes of hyperparathyroidism in the form of osteitis fibrosa. The cause for the bone lesion was not evident initially and the patient had to undergo extensive investigations for myeloma and metastatic deposit, since parathyroid cause was not at all suspected by the clinician. This case indicates that whenever one deals with bone pathology, parathyroid lesions as a cause should also be thought of and appropriate workup should be done for an early diagnosis and treatment.